Air Quality Monitoring System - Muhammad Ezzat Bin Kamaruddin (2023)
This thesis reports produced portable Air Quality Monitoring System (AQMS). This AQMS measured the air quality of three gases which are Liquefied Petroleum Gas (LPG), Carbon Monoxide (CO), and smoke followed by dust density, humidity, and temperature surrounding. This system also informed the people of current situation of air quality and send the data via Internet of Thing (Iot) called Blynk application using smartphone and also can be access by desktop. The alarm will triggered and warning will be sent once the reading exceed the safe limit range to the users. AQMS important nowadays because air quality such as haze, poisonous gases and others gaseous always spread in the air around the people and can cause the disaster to peoples, animals, plants, and earth. In addition, this AQMS was affordable and easy to carry anywhere and anytime. Different type of gaseous have different value of voltages. Technique used was measurement change of resistance of the system during clean air and present of undesire gases in air and follow by change of voltage of AQMS. The microcontroller (Arduino Mega) functioned to measure the voltage reading to determine the type of gaseous. Then the data will be sent to user by wi-fi module ESP 8266. The various experiments are performed to calibrate the accuracy of gas sensor MQ2 to get perfect reading.